Burnout in dental students: effectiveness of different methods - Juliana Alvares Duarte Bonini Campos; Paula Cristina Jordani; Miriane Lucindo Zucoloto; Fernanda Salloume Sampaio Bonafé; João Maroco
OBJECTIVE: This study was proposed to estimate the effectiveness of different screening methods of the Burnout Syndrome among dental students. MATERIAL AND METHOD: The Burnout Syndrome assessment was performed using the Oldenburg Inventory-Student survey (OLBI-SS) and the Copenhagen Inventory-Student survey (CBI‑SS). The Maslach Burnout Inventory-Student survey (MBI-SS) was used as the gold standard. The psychometric properties of the instruments were measured. The second-order hierarchical model was estimated to calculate the overall scores for OLBI-SS and CBI-SS, and ROC curves were constructed and the areas were estimated (AUROC). RESULT: A total of 235 undergraduate students participated in this study. The instruments showed an adequate reliability and validity; however three questions had to be removed from OLBI-SS and one from CBI-SS. The Exhaustion dimension of OLBI-SS, and Personal Burnout and Study related Burnout of CBI-SS presented a good discriminating capacity. CONCLUSION: CBI-SS showed higher discriminating capacity, than OLBI-SS, to identify the Burnout Syndrome (DAUROC=.172 [.103-.240]; p<.05).